EFEK ANGULAR JOINT MOBILIZATION DAN MAITLAND MOBILIZATION TERHADAP PERUBAHAN NYERI DAN RANGE OF MOTION PENDERITA FROZEN SHOULDER - Rahmat Nugraha; Nurul Zaskia; Tiar Erawan; Miuh Thahir (FORUM ILMIAH KESEHATAN, 2022)
Frozen shoulder is an inflammatory condition in which the connective tissue around the shoulder joint thickens and tightens, causing pain and loss of range of motion (ROM) both passively and actively with external rotation, abduction and internal rotation being the plane of motion that is disrupted. The method in this study is a quasi-experimental design with a randomized pretest-posttest two group, which aims to determine the difference in the effectiveness of the combination of Shortwave Diathermy (SWD) and Angular Joint Mobilization (AJM) or Shortwave Diathermy (SWD) and Maitland Mobilization in patients with Frozen shoulder in RSUD dr. La Palaloi Maros with a sample of 18 people, which were randomized into 2 groups, namely treatment group I was given SWD and AJM and treatment group II was given (SWD) and Maitland Mobilization. Paired sample t-test resulted in p value = 0.000 for external rotation, abduction and internal rotation ROM and VAS scale in treatment groups I and II, which means that there is an effect of the combination of SWD and AJM on reducing pain and increasing shoulder ROM. The results of the independent sample t-test were p = 0.000 for abduction exorotation, p = 0.006 internal rotation, and p = 0.001 on the VAS scale, which means that there is a significant difference between groups I and II. Furthermore, it was concluded that the combination of SWD and AJM was more effective than the combination of SWD and Maitland Mobilization for reducing pain and increasing shoulder ROM in patients with frozen shoulder.Keywords: shortwave diathermy; angular joint mobilization; Maitland mobilization; frozen shoulderABSTRAK Frozen shoulder adalah kondisi peradangan di mana jaringan ikat di sekitar sendi shoulder menebal dan mengencang, yang menyebabkan timbulnya nyeri dan hilangnya range of motion (ROM) secara pasif maupun aktif dengan eksternal rotasi, abduksi dan internal rotasi menjadi bidang gerak yang terganggu. Metode dalam penelitian ini adalah eksperimen kuasi dengan desain randomized pretest-posttest two group, yang bertujuan untuk mengetahui perbedaan efektivitas kombinasi Shortwave Diathermy (SWD) dan Angular Joint Mobilization (AJM) atau Shortwave Diathermy (SWD) dan Maitland Mobilization pada penderita Frozen shoulder di RSUD dr. La Palaloi Maros dengan sampel sebanyak 18 orang, yang dirandomisasi kedalam 2 kelompok yaitu kelompok perlakuan I diberikan SWD dan AJM dan kelompok perlakuan II diberikan (SWD) dan Maitland Mobilization. Paired sample t-test menghasilkan nilai p = 0,000 untuk ROM eksternal rotasi, abduksi dan internal rotasi dan skala VAS pada kelompok perlakuan I dan II, yang berarti ada pengaruh kombinasi SWD dan AJM terhadap penurunan nyeri dan peningkatan ROM shoulder. Hasil independent sample t-test adalah p = 0,000 untuk eksorotasiabduksi, p = 0,006 internal rotasi, dan p = 0,001 skala VAS, yang berarti bahwa ada perbedaan yang signifikan antara kelompok I dan II. Selanjutnya disimpulkan bahwa kombinasi SWD dan AJM lebih efektif daripada kombinasi SWD dan Maitland Mobilization untuk menurunkan nyeri dan peningkatan ROM shoulder penderita frozen shoulder.Kata kunci: shortwave diathermy; angular joint mobilization; maitland mobilization; frozen shoulder